Tanjung Siambang Community-Based Mangrove Management, Dompak Island, Tanjungpinang - Muhammad Apriansyah Daulay; Siti Arieta; Irma Dela Larasita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to produce the roles, functions and benefits of mangrove forests for people's lives, causes of damage to mangrove ecosystems, as well as efforts to preserve and rehabilitate mangrove ecosystems that have been, are being and will be carried out in the future, Tanjung Siambang. This type of research is a qualitative and in-depth survey research approach with the aim of understanding certain social situations, events, roles, or interaction groups. This study uses various techniques and various instruments to collect data for data analysis using descriptive qualitative techniques. The method used in this community research is socialization in the form of counseling to coastal communities. The result is an increase in the capacity of coastal communities regarding the benefits and preservation of mangrove ecosystems